ABSCISIC ACID INSENSITIVE3 Is Involved in Cold Response and Freezing Tolerance Regulation in Physcomitrella patens - Tan, Tinghong; Sun, Yanni; Peng, Xingji; Wu, Guochun; Bao, Fang; He, Yikun; Zhou, Huapeng; Lin, Honghui (Frontiers in Plant Science, 2017)
Transcription factor ABSCISIC ACID INSENSITIVE3 (ABI3) is known to play a major role in regulating seed dormancy, germination, seedling development as well as stress responses. ABI3 is conserved among land plants; however, its roles in non-seed plants under stress conditions have not been well characterized. In this study, we report that ABI3 is involved in freezing tolerance regulation during cold acclimation at least in part through ABA signaling pathway in moss Physcomitrella patens (P. patens). Deletion of PpABI3 (abi3-1) compromises the induction of genes related to cold response and antioxidative protection, resulting in reduced accumulation of cryoprotectants and antioxidants. In addition, photosystem II (PSII) activity is repressed in abi3-1 during cold acclimation partially due to alternations of photosynthetic protein complexes compositions. The gametophyteofabi3-1 displays severe growth inhibition and developmental deficiency under low temperature condition, while two independent complementary lines display phenotypes similar to that of wild-type P. patens (WT). Furthermore, the freezing tolerance of abi3-1 was significantly affected by deletion of PpABI3. These data revealed that PpABI3 plays an important role in low temperature response and freezing tolerance in P. patens.